Similarities and differences in the structures of 5‐bromo‐6‐hydroxy‐7, 8‐dimethylchroman‐2‐one and 6‐hydroxy‐7, 8‐dimethyl‐5‐nitrochroman‐2‐one. (6th March 2013) - Goswami, Shailesh K.; Hanton, Lyall R.; McAdam, C. John; Moratti, Stephen C.; Simpson, Jim
<x xml:space="preserve">Abstract</x> The title compounds, C11H11BrO3, (I), and C11H11NO5, (II), respectively, are derivatives of 6‐hydroxy‐5, 7, 8‐trimethylchroman‐2‐one substituted at the 5‐position by a Br atom in (I) and by a nitro group in (II). The pyranone rings in both molecules adopt half‐chair conformations, and intramolecular O—H...Br [in (I)] and O—H...Onitro [in (II)] hydrogen bonds affect the dispositions of the hydroxy groups. Classical intermolecular O—H...O hydrogen bonds are found in both molecules but play quite dissimilar roles in the crystal structures. In (I), O—H...O hydrogen bonds form zigzag C(9) chains of molecules along the a axis. Because of the tetragonal symmetry, similar chains also form along b. In (II), however, similar contacts involving an O atom of the nitro group form inversion dimers and generate R22(12) rings. These also result in a close intermolecular O...O contact of 2.686 (4) Å. For (I), four additional C—H...O hydrogen bonds combine with π–π stacking interactions between the benzene rings to build an extensive three‐dimensional network with molecules stacked along the c axis. The packing in (II) is much simpler and centres on the inversion dimers formed through O—H...O contacts. These dimers are stacked through additional C—H...O hydrogen bonds, and further weak C—H...O interactions generate a three‐dimensional network of dimer stacks.